A first experience of using failure report as a reflective tool in engineering education - Mohd Harithuddin, Ahmad Salahuddin (Kassel University Press, 2021)
The paper reports the first use of failure report as a reflective learning tool in engineering education from a university in Malaysia. Failure Report is a document that publishes and discusses failures as part of a reflective learning process for students. This reflective learning method attempts to encourage students to actually learn from failure and to take negative experiences as a learning opportunity. This paper describes the experience of introducing Failure Report as a means for engineering students to reflect their learning after completing an engineering de-sign project. The Gibbs’ Reflective Learning Model is used as the base of the reflective work. This introductory study reveals some findings on how students view and reflect on their failures and setbacks during the project work. It is noted that this was their first ever experience in doing a reflection study. Most of the students’ writing revolves around interpersonal skills like teamwork and communication. The element of ‘blame game’ is prevalent in their reports. In addition, based on this first experience, we provide several principles to follow to replicate the Failure Report activity and further recommendations for future failure reflection work.